KLaSr3(PO4)3F (Re=Tb3+/Eu3+/Eu2+): Promising Multi‐Color Luminescence Phosphors for n‐UV/UV White LEDs. Issue 11 (26th July 2016) - Guo, Qingfeng; Zhao, Chenglong; Liao, Libing; Liu, Haikun; Mei, Lefu
Abstract: Among inorganic phosphors used in solid‐state lighting, the warm white light phosphors have drawn significant attention because of their high color rendering (CRI) and appropriate warm correlated color temperature (CCT). Herein, novel green emission KLa0.90 Tb0.10 Sr3 (PO4 )3 F and red emission KLa0.90 Eu (3+) 0.10 Sr3 (PO4 )3 F phosphors were successfully synthesized for the first time. Besides, the phase constitution and photoluminescence properties were investigated in detail. The KLa0.90 Tb0.10 Sr3 (PO4 )3 F phosphor shows a green emission with a maximum at 545 nm under excitation of 231 nm, while KLa0.90 Eu (3+) 0.10 Sr3 (PO4 )3 F displays a red emission centered at 617 nm excited at 393 nm. Temperature‐dependent emission spectra reveal that these phosphors have better thermal stability and color stability. What is more, the white light emission phosphor can be generated by mixing three kinds of KLaSr3 (PO4 )3 F:Re phosphors (Re=Eu 2+, Tb 3+, and Eu 3+ ), exhibiting a CRI of ∼85 and a warm CCT of ∼3946 K. All the results indicated that the white light emission phosphor with high color rendering and appropriate warm correlated color temperature could be reached by combining these tri‐color phosphors with proper ratio. Abstract : Crystal structure and luminescence properties of KLaSr3 (PO4 )3 F: Tb 3+ /Eu 3+ phosphors with high thermal stability, and the realize of white light emission phosphor with a high CRI and warm CCT.